1994
DOI: 10.1002/pat.1994.220050304
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical properties of complexes of π‐conjugated polymers

Abstract: Novel host–guest complexes of conjugated polyimines with gallium chloride have been proposed and studied as an approach to enhance the third‐order nonlinear optical properties of the host conjugated polymers. The third‐order nonlinear optical susceptibility χ(3) (–3ω;ω,ω,ω) of two conjugated polyimines and their GaCl3 complexes, measured by third harmonic generation spectroscopy in the wavelength range 0.9 ∼ 2.4 μm, shows that χ(3) is enhanced in the nonresonant region, whereas it is reduced in the resonant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The observed large bathochromic shift of the absorption spectrum of PHOPI compared to both PPI and PMOPI can be understood in terms of intramolecular hydrogen-bonding-induced conformation change, which facilitates a more coplanar structure compared to either PPI or PMOPI. It is well-known from the X-ray crystal structure of trans - N -benzylideneaniline, a model compound of PPI, that the N -phenyl ring is twisted 55° from the plane of the imine group (CHN) due to the conjugation between the nitrogen lone-pair electrons and the π electrons on the adjacent benzene ring. , Our prior studies of GaCl 3 and diaryl phosphate complexes of conjugated polyimines showed that complexation resulted in a large bathochromic shift of the absorption spectrum relative to that of the parent polymer. , The net effect of either hydrogen bonding to the imine nitrogens of PHOPI and MO−PHOPI or their complexation by Lewis acids or protonic acids is a more coplanar molecular structure which is favorable to greater electronic delocalization in the ground state. Although there is a small bathochromic shift in going from PHOPI to MO−PHOPI, it is the intramolecular hydrogen bonding in both polymers that dominates their ground-state electronic structures.…”
Section: Resultsmentioning
confidence: 99%
“…The observed large bathochromic shift of the absorption spectrum of PHOPI compared to both PPI and PMOPI can be understood in terms of intramolecular hydrogen-bonding-induced conformation change, which facilitates a more coplanar structure compared to either PPI or PMOPI. It is well-known from the X-ray crystal structure of trans - N -benzylideneaniline, a model compound of PPI, that the N -phenyl ring is twisted 55° from the plane of the imine group (CHN) due to the conjugation between the nitrogen lone-pair electrons and the π electrons on the adjacent benzene ring. , Our prior studies of GaCl 3 and diaryl phosphate complexes of conjugated polyimines showed that complexation resulted in a large bathochromic shift of the absorption spectrum relative to that of the parent polymer. , The net effect of either hydrogen bonding to the imine nitrogens of PHOPI and MO−PHOPI or their complexation by Lewis acids or protonic acids is a more coplanar molecular structure which is favorable to greater electronic delocalization in the ground state. Although there is a small bathochromic shift in going from PHOPI to MO−PHOPI, it is the intramolecular hydrogen bonding in both polymers that dominates their ground-state electronic structures.…”
Section: Resultsmentioning
confidence: 99%
“…Polymers with significant third-order susceptibilities are typically those that also have the ability to conduct electricity, but polymers with heterocyclic laddertype structures are also very good. One of the papers published in this issue deals in detail with thirdorder susceptibilities [47].…”
Section: Nonlinear Optical Properties -mentioning
confidence: 99%